Use of antithrombotic therapy and the risk of cardiovascular outcomes and bleeding in cancer patients at the end of life: A Danish nationwide cohort study - Sarah Aldridge (Journal of Thrombosis and Haemostasis, 2025)
Background: Despite uncertain benefit-risk profile near the end of life, antithrombotic therapy (ATT) is prevalent in patients with terminal cancer. Objectives: To examine adherence and persistence with ATT in terminally ill cancer patients and investigate risks of major and clinically relevant bleeding, venous thromboembolism (VTE), and arterial thromboembolism (ATE) by ATT exposure. Methods: Using a Danish nationwide cohort of terminal cancer patients, ATT adherence in the year following terminal illness declaration was measured by the proportion of days covered (PDC) by prescription. Discontinuation was defined as a treatment gap of ≥30 days between prescription renewals. One-year cumulative incidences of bleeding complications, VTE, and ATE were calculated, considering the competing risk of death. Results: During 2013-2022, 86,732 terminally ill cancer patients were identified (median age 75 years, 47% female, median survival 57 days). At terminal illness declaration, 37.5% were receiving ATT (66.6% platelet inhibitors, 23.0% direct oral anticoagulants (DOAC), and 10.4% vitamin K antagonists (VKA)). The mean PDC was 88% (SD 30%), highest among platelet inhibitor users (mean PDC 89%) and lowest among VKA users (73%). One-year ATT discontinuation incidence was 7.9% (95% CI 7.7%-8.1%). Most patients continued ATT until death (74.8% platelet inhibitors, 58.8% DOACs, 61.6% VKAs). Patients receiving ATT had a lower one-year VTE risk but higher risks of ATE and major bleeding. Conclusion: Despite uncertain benefit-risk profile, most terminally ill cancer patients continue ATT until the end of life. These findings provide insights into current ATT utilisation and discontinuation dynamics in the challenging context of terminal illness.